Financial risk management for Islamic banking and finance - Akkizidis, Ioannis S.; Khandelwal, Sunil Kumar (Hampshire ; New York : Palgrave Macmillan, 2008)
"Risk management for Islamic banking financial products and services is one of the greatest challenges that many westernised, as well as Islamic banks, are facing today. This book presents a common framework on how to efficiently manage the risks faced and minimise the overall degree of Islamic financial risks. It is a valuable guide for those working in both non-Islamic and Islamic finance."--BOOK JACKET.
Principles of Islamic finance -- Risk management issues in Islamic financial contracts -- Basel II and IFSB for Islamic financial risk -- Credit risks in Islamic finance -- Market risks in Islamic finance -- Operational risk in Islamic finance.
Includes bibliographical references and index.
Keywords: Banks and banking -- Islamic countries; Financial risk management -- Islamic countries; Finance -- Islamic countries; Banks and banking -- Religious aspects -- Islam; Finance -- Religious aspects -- Islam